Pengaruh Pengembangan Karir Terhadap Kinerja Pegawai Pada PT. Nubika Jaya Kabupaten Labuhan Batu Selatan - Mhd Faisal Anwar Afandi Rambe; Muhammad Ikhsan Harahap (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to explain the analysis of the influence of career development on employee performance. Employee performance is a very important factor for the success of the company. The population and sample this time are all 50 employees of PT Nubika Jaya. The data were analyzed using path analysis techniques. The results of the data state that career development and work motivation have a positive and significant effect on employee performance. Career development will also have a positive effect on work motivation, with work motivation being able to mediate the influence of career development on employee performance.